Angiogenic Markers and Cardiovascular Indices in the Prediction of Hypertensive Disorders of Pregnancy. Issue 6 (June 2017) - Verlohren, Stefan; Perschel, Frank H.; Thilaganathan, Baskaran; Dröge, Lisa Antonia; Henrich, Wolfgang; Busjahn, Andreas; Khalil, Asma
Abstract : Angiogenic and antiangiogenic factors have proven to be an accurate predictive means of preeclampsia. Echocardiographic studies have shown that women with preeclampsia exhibit significant cardiovascular strain, especially early-onset preeclampsia. The aim of this study is to determine preeclampsia risk with soluble fms-like tyrosin kinase 1/placental growth factor ratio, serum NT-proBNP (N-terminal pro B-type natriuretic peptide), and biophysical markers of cardiovascular function in a prospective case–control study. We examined a cohort of 110 pregnant women with uneventful pregnancy outcome (controls) and 129 with hypertensive pregnancy disorders, including 77 with preeclampsia and 52 with pregnancy-induced hypertension. Cardiac indices were obtained with a USCOM-1A monitor, and soluble fms-like tyrosin kinase 1, placental growth factor, and NT-proBNP were measured in serum samples on automated platforms. Logistic regression, as well as Cox proportional hazard analysis, was performed. There were significant contributions from all variables tested, except for heart rate, stroke volume index, and cardiac index to the prediction model. When testing accuracy of respective markers in combination (full model) versus individual markers (soluble fms-like tyrosin kinase 1/placental growth factor ratio and total peripheral resistance) was compared. The soluble fms-like tyrosin kinase 1/placental growth factor ratio and total peripheral resistance performed as good as the full model, except for hypertensive pregnancy disorders and pregnancy-induced hypertension, where the full model performed better. The additional assessment of biophysical and biochemical markers of cardiovascular strain in pregnancy increases the detection of the composite group of hypertensive pregnancy disorders, while not significantly improving detection of preeclampsia alone. This offers a more precise insight into the pathogenesis of the disease, as well as offering a window for intervention, possibly decreasing cardiovascular mortality in these women. Abstract : Supplemental Digital Content is available in the text.